Editorial - Ensor, Jason; Polak Iva; Van Der Merwe, Peter (2007)
Uses of the ‘other’ in politics are never for minor effects. Before Australia could back US-led ‘pre-emptive strikes against strangers’ in other lands and exclude foreigners in leaky boats from ever reaching our shores, a re-imaging of the ‘other’ in league with federal agendas needed to be sufficiently underway to curb voter backlash during the late 2001 Australian election and beyond. New and familiar national fictions about and towards the ‘other’ were trotted out. ‘Inhumane’, ‘children overboard’, ‘economic refugees’, ‘queue-jumpers’, ‘a just war’, ‘war on terror’, ‘if you want a Taliban for a neighbor, vote Labor’, ‘a pipeline for terrorists’ – indeed, these were offered by politicians as alibis to lower the threshold of personal responsibility we might have otherwise felt towards those in need who had travelled far and those who lived in oppressive territories even further away. 21 papers by various scholars included in Other Contact Zones explore mechanisms of responsibility and avoidance, the politics of gender representation, sings of sexual deviances written on the convict body, the invention of the white woman as an object of fantasy in captivity narratives of early colonial Australia, the creation of multicultural senses of belonging, and the complexities of identity construction in the face of mechanisms of silence and misrecognition.
Projekt MZOS
ENG